The Path to the Software-Defined Radio Receiver - Abidi, A.A. (IEEE journal of solid-state circuits, 2007)
After being the subject of speculation for many years, a software-defined radio receiver concept has emerged that is suitable for mobile handsets. A key step forward is the realization that in mobile handsets, it is enough to receive one channel with any bandwidth, situated in any band. Thus, the front-end can be tuned electronically. Taking a cue from a digital front-end, the receiver's flexible analog baseband samples the channel of interest at zero IF, and is followed by clock-programmable downsampling with embedded filtering. This gives a tunable selectivity that exceeds that of an RF prefilter, and a conversion rate that is low enough for A/D conversion at only milliwatts. The front-end consists of a wideband low noise amplifier and a mixer tunable by a wideband LO. A 90-nm CMOS prototype tunes 200 kHz to 20-MHz-wide channels located anywhere from 800 MHz to 6 GHz